I am mismatched, I am doing well: horizontal job-education mismatches and workers’ Well-being - Laila Meiliyandrie Indah Wardani; Rahmat Dwi Syaputra; Mohd. Dahlan A. Malek; Erna Risnawati; Mayang Safira Kartikawati; Dyah Ayu Sekarini; Rizki Dawanti; Prahastia Kurnia Putri; Melani Aprianti; Dhani Irmawan (ResearchGate, 2024)
Objectives: This study examines whether psychological empowerment plays a role in job crafting and employee well-being for workers who face horizontal educational mismatches. A horizontal educational mismatch could be defined as a mismatch between the field of education and current occupation. This study shows that horizontal educational mismatches which are increasingly commonplace in society, especially in Indonesia, may affect the well-being of workers. Employee well-being describes the overall well-being of employees, such as physical, psychological, and individual aspects. Methods: The study’s respondents are 361 Indonesian workers with horizontal educational mismatches. The study’s tools are employee well-being scale (EWBS), job crafting questionnaire (JCQ), and psychological empowerment questionnaire (PEQ). The measuring tools were adapted into the Indonesian language, and data was analyzed by Andrew F. Hayes’s simple regression mediation model no.4 PROCESS v4.0. Results: The study reveals that psychological empowerment facilitates job crafting and employee well-being for workers with horizontal educational mismatches. It also shows that employees who are psychologically empowered are those who are supported in taking responsibility for enhancing their performance and their contribution to the organization. As a result of the increased demand for productivity, employees must enhance their skills and knowledge to achieve higher job demands instead of simply establishing opportunities for wellbeing and self-development. That is, workers are given the abilities and resources required to compensate for the shortages caused by the horizontal educational mismatch they face. Conclusions: This study fills in a research gap by shedding light on the indirect effect a horizontal educational mismatch might have on workers’ competence and will-being.